Problems of geodynamics of the Ukrainian shield in Precambrian - O. Gintov (Геофизический журнал, 2015)
The main achievements of Ukrainian geologists and geophysicists in the studies of processes of geodynamic development of the Ukrainian Shield in the Archean—Early Proterozoic are considered as well as the main problems and tasks for their solving. For further effective studies of Precambrian geodynamic processes it is proposed to increase the extent of examinations of the deep structure of the Shield by laying international geo-traverse of deep seismic sounding, which crosses the typomorphic geodynamic zoning of the Shield in latitudinal direction.  The extent of radiogeochronologic and deep petrologic studies of the Shield and their integration with paleomagnetic and tectonophysical data is also important.